Analyzing telecommunication coverage using GIS technique / Ratnah Mappiakka - Mappiakka, Ratnah (2015)
Telecommunication coverage in Universiti Teknologi MARA (UiTM) and residential areas in Kota Samarahan, Sarawak need to be analyze because the study area received very poor signal coverage from the existing tower stations. The signal strength data from all the five (5) i.e. Kota Samarahan station, TM Kota Samarahan station, Bank Islam station, Universiti Malaysia Sarawak (Unimas) station and UiTM Kuching station are observed manually by driving through and using Test Mobile System (TEMS) instrument. The collected data are then transferred to Geographical Information System (GIS) software for further analysis. The aim of this research is to utilize GIS techniques to analyze telecommunication coverage of the study area. To achieve the general aim of the study, the objectives are as follows: i) to determine mobile phone signal strength of the study area, ii) to identify/map signal strength based on different tower station configurations and iii) to propose new tower configuration or setup such as the height of the tower station, antenna orientation and location of the tower station. The study area covers the whole area of Sarawak campus and residential areas of Kota Samarahan. The software used for this study are Map Info Version 7, ArcGIS Version 9.3 and Global Mapper Version 10.02. Viewshed analysis, antenna orientation analysis and combination between viewshed analysis and antenna orientation analysis are used to evaluate the different tower stations configurations. Findings from this study have shown that the mobile phone signal strength of the study area can be separated into five (5) categories. There is the very strong signal strength reading records from 0 dBm to -36 dBm, strongest signal strength started from -37 dBm to -53 dBm, the moderate of signal strength reading marked from -54 dBm to -64 dBm, the weakness of signal strength shown in the map with the reading from -65 dBm to -76 dBm and the very weakness of the signal strength over the study area recorded from -77 dBm to -82 dBm. It was also found that the eastern part of the study area received very strong coverage as compared to the other areas because there are three (3) nearby stations (i.e. Kota Samarahan station, TM Kota Samarahan station and Bank Islam station). The south western part of the study area proved to have the weakest signal strength because the antenna orientation from the nearest station such as UiTM Kuching station and Unimas station are not covered the whole part of that area. This study proposed different tower station height and the construction of new tower stations near the western and south-western part of the study area to improve signal strength in problematic areas. As an overall conclusion, this research proved that the implementation of GIS techniques can be used to identify the mobile phone signal strength and can be used to propose the optimum tower configuration over the study area.